Curriculum and teacher assessment practices in mathematics learning: Alignment with higher order thinking skills in Indonesian secondary schools - Zana, Firdha Mahrifatul; Sa'dijah, Cholis; Susiswo; Anwar, Lathiful; Zulnaidi, Hutkemri (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
Higher-Order Thinking Skills (HOTS) are an essential element in education that must be integrated into curricula and classroom assessments. In Indonesia, educational initiatives have increasingly emphasized the incorporation of HOTS into both curriculum design and assessment practices. However, prior research has primarily focused on the challenges faced by teachers in developing HOTS-based assessments and aligning their teaching with curriculum demands. This study aims to investigate how the Indonesian mathematics curriculum integrates HOTS and evaluate the alignment between the curriculum objectives and teacher-developed assessments in fostering HOTS. The study employed a descriptive qualitative approach and was conducted in two Indonesian high schools, one located in an urban area and the other in a regional setting. A total of 15 mathematics teachers from grades ten, eleven, and twelve participated in the research. Data collection methods included focus group discussions, document analysis of mathematics assessments, and semi-structured interviews. The analysis employed Anderson and Krathwohl’s Taxonomy to categorize cognitive levels. Findings reveal that the Indonesian Mathematics Curriculum predominantly emphasizes Low-Order Thinking Skills (LOTS), and teacher-developed assessments are largely aligned with these LOTS-focused objectives. Furthermore, even when curriculum indicators aim to target HOTS, teachers often struggle to design assessments that effectively evaluate students’ higher-order cognitive abilities. These findings highlight a significant gap between curriculum goals and the practical implementation of HOTS in assessments. The results provide valuable insights for curriculum developers, suggesting the need for a curriculum redesign that places greater emphasis on HOTS. Additionally, the study underscores the importance of professional development initiatives to equip teachers with the skills necessary to design and implement HOTS-based assessments. This research contributes to advancing educational practices and policies that prioritize the integration of HOTS into teaching and assessment frameworks.